Adjuncts and the HPSG binding theory - Walker, Heike (Proceedings of the 18th International Conference on Head-Driven Phrase Structure Grammar, 2011)
The HPSG binding theory in Pollard and Sag (1994) cannot account for the binding-theoreticinteraction between main clause and adjunct-internal elements. Following Hukari and Levine (1995), Iclaim that structural configurations must be taken into account. In this article, I present arevised version of Hukari and Levine's configurational relation called v(alence-based)-c-command andpropose that Principle C must involve this relation in addition to the obliqueness-based relation ofo-command. New data are provided that strongly support the proposed revision of the HPSG bindingtheory. Finally, I argue that Principle C is syntactic rather than pragmatic in nature.